2012
DOI: 10.1038/eye.2012.132
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of thyroid-associated ophthalmopathy in clinically euthyroid Korean patients

Abstract: Aim To compare clinical characteristics and thyroid-stimulating hormone receptor antibodies (TRAbs) in thyroid-associated ophthalmopathy (TAO) in euthyroid Korean patients with those in hyperthyroid patients. Methods Clinical activity scores (CASs), modified NOSPECS scores, exophthalmometry values, prevalence of optic neuropathy, restrictive myopathy and lid retraction, and the positivity and levels of TRAb (thyrotropin-binding inhibitor immunoglobulin (TBII) and thyroidstimulating immunoglobulin (TSI)) were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 26 publications
2
27
0
Order By: Relevance
“…Further, it has been shown that euor hypothyroid TAO can be associated with ocular myasthenia gravis (15), with an ectopic thyroid gland (16), or with papillary thyroid microcarcinoma (17,18). Single studies have suggested that euthyroid and primarily hypothyroid patients develop milder and significantly more asymmetrical TAO (6,19). Severe TAO is rare in these cases but a few case reports have described primarily euthyroid or hypothyroid TAO patients with clinically severe TAO requiring systemic immunosuppression (20).…”
Section: Introductionmentioning
confidence: 95%
“…Further, it has been shown that euor hypothyroid TAO can be associated with ocular myasthenia gravis (15), with an ectopic thyroid gland (16), or with papillary thyroid microcarcinoma (17,18). Single studies have suggested that euthyroid and primarily hypothyroid patients develop milder and significantly more asymmetrical TAO (6,19). Severe TAO is rare in these cases but a few case reports have described primarily euthyroid or hypothyroid TAO patients with clinically severe TAO requiring systemic immunosuppression (20).…”
Section: Introductionmentioning
confidence: 95%
“…Case reports of euthyroid TAO several decades ago also describe patients with ocular signs of TAO and normal thyroid function without previous history of hyperthyroidism. 16 17 To our knowledge, our study is the first to report euthyroid TAO following total thyroidectomy. In the present study, case 6 demonstrated severe active TAO despite undergoing total thyroidectomy for a benign thyroid mass 10 years prior to the ophthalmology department visit.…”
Section: Discussionmentioning
confidence: 68%
“…However, euthyroid patients are more likely to have unilateral eye involvement as compared to hyperthyroid individuals. Jang et al reported increased incidence of unilateral eye involvement (79.2%) in euthyroid patients as compared to patients with hyperthyroidism (27.3%) (8). Eckstein et al also reported increased incidence of asymmetric eye involvement in euthyroid patients as compared to hyperthyroid patients (9).…”
Section: Case Reportmentioning
confidence: 99%